2010
DOI: 10.14314/polimery.2010.503
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization of functional cyclotrisiloxanes – a reactivity comparison

Abstract: Od RedakcjiW niniejszym podwójnym numerze naszego czasopisma 6 pierwszych artyku³ów dotyczy treoeci wyst¹pieñ przedstawionych w ramach Sekcji Polimerowej na 52. ZjeŸdzie PTChem i SITPChem, który odby³ siê w £odzi, w dniach 12-16 wrzeoenia 2009 r.Summary -Kinetics of controlled simultaneous copolymerization of hexamethylcyclotrisiloxane (D 3 ) with functional cyclotrisiloxanes was studied using n-BuLi in THF as initiator. Trifunctional (MeXSiO) 3 (X 3 ), where X = vinyl, trifluoropropyl or chloropropyl group, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…The rate constants of homopolymerization of normalD3Ph and normalD3normalF were independently determined by kinetic experiments (Tables and ). Notably, the values reported herein should be considered as the apparent reactivity ratios, which in fact may not be constant because the apparent rate constants may vary depending on the concentrations of the monomers and initiator; however, still may be useful for predicting the polymer composition in the limited range of concentrations of the monomers and initiator . The apparent reactivity ratios of normalD3Ph and normalD3normalF verified the differences in the reactivity when the copolymerization was initiated by CF 3 SO 3 H and Ph 2 Si(OLi) 2 , respectively; and one of the reactivity ratios greater than one for both the methods further indicated that the copolymers contained the gradient microstructures which was finally confirmed by 29 Si NMR, GPC, and DSC analysis.…”
Section: Resultsmentioning
confidence: 63%
See 4 more Smart Citations
“…The rate constants of homopolymerization of normalD3Ph and normalD3normalF were independently determined by kinetic experiments (Tables and ). Notably, the values reported herein should be considered as the apparent reactivity ratios, which in fact may not be constant because the apparent rate constants may vary depending on the concentrations of the monomers and initiator; however, still may be useful for predicting the polymer composition in the limited range of concentrations of the monomers and initiator . The apparent reactivity ratios of normalD3Ph and normalD3normalF verified the differences in the reactivity when the copolymerization was initiated by CF 3 SO 3 H and Ph 2 Si(OLi) 2 , respectively; and one of the reactivity ratios greater than one for both the methods further indicated that the copolymers contained the gradient microstructures which was finally confirmed by 29 Si NMR, GPC, and DSC analysis.…”
Section: Resultsmentioning
confidence: 63%
“…Initiation was assumed to be instantaneous, although the model assuming rapid but not instantaneous initiation has also been examined. This complication did not have any significant impact on the results dtrue[normalD3normalPnormalhtrue]dnormalt = knormalPnormalPtrue[normalPnormal*true]true[normalD3normalPnormalhtrue] + knormalFnormalPtrue[normalFnormal*true]true[normalD3normalPnormalhtrue] dtrue[normalD3normalFtrue]dnormalt = knormalPnormalFtrue[normalPnormal*true]true[normalD3normalFtrue] + knormalFnormalFtrue[normalFnormal*true]true[normalD3normalFtrue] dtrue[normalPnormal*true]dnormalt= d[]|F*dnormalt = knormalFnormalPtrue[normalFnormal*true]true[normalD3normalPnormalhtrue] knormalPnormalFtrue[normalPnormal*true]true[normalD3normalFtrue] …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations